(untitled) (International Seven Journal of Multidisciplinary, 2024)
The complexity of today’s reality drives the insertion of new ideas into the educational context, with empowering projects that impact social, economic and environmental systems, generating sustainable opportunities. Entrepreneurship in higher education institutions in Brazil requires innovative approaches, beyond isolated disciplines, to promote a sustainable entrepreneurial culture and contribute to community development. Faced with social needs, questions arise about projects that promote individual and collective training, meeting demands for interprofessional training in the social, economic and environmental spheres.